Current Approaches to the Treatment of Hunter Syndrome - Ekaterina Yu. Zakharova; Elena Yu. Voskoboeva; Alla N. Semyachkina; Nato D. Vashakmadze; Amina I. Gamzatova; Svetlana V. Mikhailova; Sergey I. Kutsev (Педиатрическая фармакология, 2018)
Mucopolysaccharidosis type II (MPS II; Hunter syndrome) is an X-linked hereditary disorder associated with a deficiency of iduronate2-sulfatase (IDS). IDS deficiency provokes the accumulation of dermatan sulfate and heparan sulfate in different tissues. Clinical manifestations of MPS II are heterogeneous and involve different organs. Two phenotypes are distinguished: attenuated or severe; classification is based on central nervous system impairment signs. The review provides data on the current treatments opportunities for Hunter syndrome and perspectives for development of new therapeutic approaches. Current treatment includes intravenous enzyme replacement therapy (ERT), hematopoietic stem cell transplantation, and symptomatic treatment. Intravenous enzyme replacement therapy does not promote the enzyme to penetrate the blood-brain barrier which leads to the treatment failure for neurological signs and symptoms; hematopoietic stem cell transplantation has high risk of post-transplantation complications but can improve some neurological problems. Intrathecal ERT, substrate reduction, pharmacological chaperones, and gene therapy are currently under investigation as therapies for severe form of MPS II. Development of new approaches to treatment of Hunter syndrome and other hereditary diseases is extremely vital.